Avaliação in vitro da atividade do ibuprofeno frente a isolados de Candida spp. Resistentes ao fluconazol e sua atividade contra biofilme formado - Sampaio, Letícia Serpa (2017)
In recent years, there has been an increase in the incidence of opportunistic fungal infections. Candida species have been documented as an important cause of infections and related to high morbidity and mortality among hospitalized patients, increasing hospital costs and length of stay,configuring an important public health problem. Most fungal infections are associated with biofilm formation, which represents an increase in antifungal resistance. In addition to this problem, there are few antifungal agents available. That way, it is necessary to search for new therapeutic options and in this context the drug repurposing appears, proposing a “new eyes” for drugs with other therapeutic indications. Ibuprofen is a non-steroidal anti-inflammatory drug and some researchers have reported its activity against Candida spp. The present study aimed to evaluate the activity of ibuprofen against fluconazole resistant Candidaspp., in planktonic and biofilm forms, using broth microdilution techniques, flow cytometry and comet assay. Ibuprofen showed activity against nine strains of Candida spp. (2 C. albicans, 5C. tropicalis, 2 C. parapsilosis)with the minimum inhibitory concentration (MIC) ranging from 6,5 to 13mM and it did neitherinduced reactive oxygen species (ROS) generation nor DNA damage on equivalent concentrations to MIC in strains of C. albicans(MIC=6,5mM), C. tropicalis (MIC=13mM) and C. parapsilosis(MIC=13mM).It was found that ibuprofen reduces cell viability, promotes mitochondrial depolarization and enhancing phosphatidylserine externalization, suggesting cell death by apoptosis. The cell viability of the biofilms was determined by assaying reduction of the tetrazolium salt (MTT) and it was verified that ibuprofen promoted about 50% reduction in cell viability at MIC concentration (13mM)in C. albicans, C. tropicalis and C. parapsilosis isolates (p <0,05). That way, we concluded that ibuprofen is able to inhibit the growth of fluconazole resistant Candida spp. in vitro both in planktonic cells and biofilmformed, suggestingthat this drug has potential to act as antifungal compound with apoptotic activity.